ОЦІНКА ГЛИБИН ЗАЛЯГАННЯ ВЕРХНЬОЇ МЕЖІ СІРКОВОДНЕВОЇ ЗОНИ ЧОРНОГО МОРЯ ЗА ДАНИМИ БУЇВ 2015-2022 РР. - Попов, Ю.І.; Диханов, Ю.М.; Коморін, В.М. (Marine Ecological Journal, 2022)
Biocenoses of the Black Sea are ones of the most vulnerable natural systems of the Earth. About 87 % of the Black Sea water volume is occupied by the hydrogen sulfide zone. Ecosystems of the thin layer of the upper oxygen zone are extremely sensitive to both anthropogenic impact and the influence of natural factors, the intensification of which has been observed recently due to rapid global climate change. The aim of the work is to assess the depth appearance, spatial distribution and change of the upper boundaries of the hydrogen sulfide zone of the Black Sea with the buoys ARGO data. In the article it was used hydrophysical and hydrochemical information obtained from the oceanographic database of the ARGO project in the Black Sea for the period from March 2015 to March 2022, such as: temperature, salinity, dissolve oxygen and hydrogen sulfide. A total of 591 arrays were analysed. A critical analysis of the quality of the selected information was carried out. The profile data has been adjusted. When processing the material, the method of optimal interpolation, graphic and statistical analysis were used. The original programs of UkrSCES were used. It was concluded according to the results of the work that the upper boundary of the anaerobic zone of the Black Sea in areas of buoy drift was located at depths of 100-180 meters. The difference in the indications for determining the boundaries according to two independent criteria: the depth of the water bodies with a hydrogen sulfide concentration of 3 μmol/kg, and the depth of the iso-surface of the conditional density of 16.18, which on average fluctuated within ±7 meters. In some areas, significant fluctuations in the upper limit of the anaerobic zone, caused by the influence of local hydrodynamic vortices, or removal of intrusive water from the Bosphorus Strait, were noted. The spatiotemporal variability of the sub-oxygen zone in the areas of buoy-profilometer drift, as well as the areas where this layer has minimum and maximum power.